A hierarchically structured PtCo nanoflakes–nanotube as an electrocatalyst for methanol oxidation. Issue 5 (22nd March 2017) - Yu, Dongbo; Shamsaei, Ezzatollah; Yao, Jianfeng; Xu, Tongwen; Wang, Huanting
Abstract : A novel PtCo nanoflake–nanotube architecture was prepared through a galvanic replacement approach. Due to the unique structure, it exhibited excellent electrocatalytic performances for methanol oxidation. Abstract : A novel PtCo nanoflake–nanotube architecture was constructed by using a Co metal nanowire array as the sacrificial template through a galvanic replacement reaction. The as-prepared hierarchical structure achieved an effective utilization of Pt and exhibited much better activity and stability for electrocatalytic oxidation of methanol than the commercial Pt/C catalyst.